Sustainable labor migration through vocational education and training providers? Conditions of access and accessibility in the public-private (continuing) VET sector - Klaus, Frieda; Kühn, Ida Kristina (Frontiers in Education, 2026)
ContextDue to the shortage of skilled workers, Germany is already recruiting skilled workers from abroad, especially from countries outside the EU. The Skilled Labour Immigration Act (FEG), introduced in 2020 and amended in 2023, regulates the migration of skilled workers. In addition to legally regulated access, other measures also play a role in ensuring that skilled migrants remain in Germany. For this reason, the article examines the questions of how vocational education and training (VET) providers initiate the integration of migrants, which structural elements target capabilities, and how they perceive their own potential.MethodsAs part of an EU-funded project, a document analysis and problem-centered interviews were conducted. A total of 40 stakeholders from different status groups in Germany (e.g., employers, VET institutions) from various sectors were interviewed. Using an analytical framework based on Heckmann’s integration theory and Nussbaum’s capability approach, the interviews were analyzed with regard to the research questions focussing on four specific capabilities.FindingsThe analysis revealed that most accessibility measures focused on the structural dimension of integration. To promote social participation, a greater social inclusion is required. All identified measures also showed potential for the four specific capabilities, but only to a limited extent. VET providers are aware of the importance of labor migration and the associated responsibilities, but more general initiative is needed, as much of the work has so far been based on individual commitment.ConclusionA holistic view of the integration process of migrants requires the inclusion of these individuals’ perspectives. It also became clear that the conversion factors of migrants play an essential role in transforming capabilities into functionings, so that the analyzed promotion of capabilities merely reflects potential and is determined by the individual resources of migrants.